Effect of tacrolimus with mycophenolate mofetil or cyclophosphamide on the renal response in systemic lupus erythematosus patients - Siqin Sun; Xueyi Zhang; Qingqing Guo; Xiaojun Tang; Wei Shen; Jun Liang; Genhong Yao; Linyu Geng; Shuai Ding; Hongwei Chen; Hong Wang; Bingzhu Hua; et al. (BMC Rheumatology)
Abstract Objective This study aimed to determine the therapeutic efficacy of tacrolimus (TAC) with mycophenolate mofetil (MMF) or cyclophosphamide (CYC) on the renal response in systemic lupus erythematosus (SLE) patients. Methods A retrospective cohort study based on medical data was conducted among SLE patients who took at least one of the following medicines in 2010–2021: TAC, MMF and CYC. The odds ratio (OR) and 95% confidence interval (CI) were calculated, and the synergistic interaction was estimated using logistic regression models. Results Among 793 SLE patients, 27.9% patients (221 cases) achieved CR after at least 3 months. The TAC use was positively associated with CR with an adjusted OR (95% CI) of 2.82 (1.89, 4.22) overall and in subgroups of SLE patients with SLEDAI scores > 12, moderate or severe urinary protein and comorbidities. The dose-response effect on CR was also observed at TAC doses greater than 4 mg/d and more than 180 days, with adjusted ORs (95% CIs) of 5.65 (2.35, 13.55) and 3.60 (2.02, 6.41), respectively. Moreover, the combined effect of TAC with MMF or CYC was better than that of monotherapy, there was significant synergistic interactions with adjusted ORs (95% CIs) of 2.43 (1.20, 4.92) and 3.14 (1.49, 6.64), respectively, and similar results were observed for the combination of different doses of TAC with MMF or CYC. Conclusion TAC can effectively alleviate the condition of patients with SLE and may interact with MMF or CYC, which suggests that the combination therapy of TAC with MMF or CYC may produce greater benefits for patients with SLE. Trial registration This is a purely observational study that does not require registration.